1973
DOI: 10.1002/bjs.1800600813
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of fibre-optic endoscopy in the operated stomach

Abstract: Fibre-optic instruments have been used on 212 occasions to examine 177 patients who were symptomatic after peptic ulcer surgery. A diagnosis other than gastritis was reached in 83 patients, including 46 ulcers. Five ulcers were not seen-4 as a result of using inadequate equipment early in the series. Radiology detected only 60 per cent of the ulcers and raised many false-positive diagnoses. Expert review of the radiographs corrected many originally mistaken interpretations. Retained suture materials were seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…This was not so with all the remaining patients but the results for these were the same as for those assessed blind. The high incidence of endoscopic abnormalities was similar to other series after gastric surgery (Hirshchowitz and Luketic, 1971;Cotton et al, 1973). The extent of changes varied with the operation per- formed, the most frequent and severe being after Billroth II partial gastrectomy and the least after proximal gastric vagotomy.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This was not so with all the remaining patients but the results for these were the same as for those assessed blind. The high incidence of endoscopic abnormalities was similar to other series after gastric surgery (Hirshchowitz and Luketic, 1971;Cotton et al, 1973). The extent of changes varied with the operation per- formed, the most frequent and severe being after Billroth II partial gastrectomy and the least after proximal gastric vagotomy.…”
Section: Discussionsupporting
confidence: 86%
“…Yet the relevance of this is still controversial. Although Cotton et al (1973) thought that hyperaemia was not significant, others (Keighley et al, 1975;O'Neill et al, 1975) have found it more common in patients with symptoms. There is confusion about the nomenclature of these mucosal changes, some authors have referred to the abnormal endoscopic findings as gastritis (Stempien et al, 1971).…”
mentioning
confidence: 95%
“…1 The histopathological features of the changes seen in the gastric mucosa exposed to biliary and duodenopancreatic reflux after partial gastrectomy, particularly Billroth II operations, were described in the 1960s and 1970s and generically referred to as post-operative gastritis [2][3][4][5] ; their possible premalignant nature was later noted in cohorts of operated patients. [6][7][8][9] Between 1983 and 1986, Dixon's group in Liverpool published a series of papers in which they systematically described these changes and proposed 'bile reflux gastritis' as a distinct clinicopathological entity.…”
Section: Introductionmentioning
confidence: 99%
“…William Beaumont in 1833 documented an association between bile in stomach with gastric mucosal damage [33]. Morphological features observed in such gastric mucosa were described much later in the 1960s and 1970s, were referred to as post-operative gastritis with malignant potential [34][35][36][37][38][39][40]. In the 1980s, these mucosal changes were referred to as bile reflux gastritis [41,42].…”
Section: Drugs and Chemical-related Gastritis Or Reactive Gastropathymentioning
confidence: 99%